2014
DOI: 10.4081/rt.2014.5350
|View full text |Cite
|
Sign up to set email alerts
|

Connection between Cell Phone use, p53 Gene Expression in Different Zones of Glioblastoma Multiforme and Survival Prognoses

Abstract: The aim of this paper is to investigate p53 gene expression in the central and peripheral zones of glioblastoma multiforme using a real-time reverse transcription polymerase chain reaction (RT-PCR) technique in patients who use cell phones ≥3 hours a day and determine its relationship to clinicopathological findings and overall survival. Sixty-three patients (38 males and 25 females), diagnosed with glioblastoma multiforme (GBM), underwent tumor resection between 2008 and 2011. Patient ages ranged from 25 to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…In a study it was found that use of mobile phones for ≥3 hours a day was associated with increased risk for the mutant type of p53 gene expression in the peripheral zone of glioblastoma multiforme, the most malignant glioma type. Furthermore, this mutation increase was statistically significant correlated with shorter overall survival time [54]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study it was found that use of mobile phones for ≥3 hours a day was associated with increased risk for the mutant type of p53 gene expression in the peripheral zone of glioblastoma multiforme, the most malignant glioma type. Furthermore, this mutation increase was statistically significant correlated with shorter overall survival time [54]. …”
Section: Resultsmentioning
confidence: 99%
“…One interesting aspect is the increased risk for the mutant type of the p53 gene expression in glioblastoma multiforme associated with use of mobile phones [54]. The mutation is involved in disease progression and shorter survival was found in patients with the mutant gene.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 protein is a transcription factor that plays a vital role in regulating cell growth, DNA repair and apoptosis, and p53 mutations are involved in disease progression. In a recent study it was found that use of mobile phones for ≥3 h a day was associated with increased risk for the mutant type of p53 gene expression in the peripheral zone of astrocytoma grade IV, and that this increase was statistically significant correlated with shorter overall survival time [ 20 ]. The study was rather small (n = 63) and no data on latency of mobile phone use was given.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a decreased survival of patients with glioblastoma multiforme associated with long-term use of wireless phones was reported [ 15 ]. Another study reported mobile phone use for ≥3 h a day to be associated with a consistent pattern of increased risk for the mutant type of p53 gene in the peripheral zone of the glioblastoma, and that this increase was statistically significant correlated with shorter overall survival time [ 16 ].…”
Section: Introductionmentioning
confidence: 99%